2021
DOI: 10.3389/fncel.2021.673782
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Mechanism of Sodium Binding to SERT Using Direct Simulations

Abstract: The serotonin transporter (SERT) terminates neurotransmission by transporting serotonin from the synapse into the pre-synaptic nerve terminal. Altered SERT function leads to several neurological diseases including depression, anxiety, mood disorders, and attention deficit hyperactivity disorders (ADHD). Accordingly SERT is the target for their pharmacological treatments, but also targeted by multiple drugs of abuse. Transport of serotonin by SERT is energized by the transmembrane electrochemical gradient of so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 56 publications
3
25
0
Order By: Relevance
“…In this study, we capture the motions leading to the sequestering of substrate 5HT through occlusion of hSERT in a cholesterol-containing phospholipid bilayer that mimics the physiological cell membrane. The unbiased all atom MD simulations confirmed that the outward-open state of ion-bound hSERT is stable in the absence of 5HT, which is consistent with experimental data showing that the outward-facing conformation of SLC6 transporters is stable in the presence of the co-transported ions ( 26 , 28 , 30 ).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In this study, we capture the motions leading to the sequestering of substrate 5HT through occlusion of hSERT in a cholesterol-containing phospholipid bilayer that mimics the physiological cell membrane. The unbiased all atom MD simulations confirmed that the outward-open state of ion-bound hSERT is stable in the absence of 5HT, which is consistent with experimental data showing that the outward-facing conformation of SLC6 transporters is stable in the presence of the co-transported ions ( 26 , 28 , 30 ).…”
Section: Discussionsupporting
confidence: 86%
“…We used extensive bias-free equilibrium all atom molecular dynamic simulations (40 μs total simulation time) to investigate the substrate-induced occlusion of hSERT, thereby avoiding the danger of inducing structural changes which could deviate from the lowest energy path. Simulations of sodium- and chloride-bound hSERT show that ion binding stabilizes the outward-open state ( 26 , 27 , 28 ), while binding of 5HT to the S1 changes the conformational equilibrium leading to hSERT occlusion. We could identify the sequence of events essential for hSERT occlusion and discovered that TM1b and TM6a move remarkably independently of each other.…”
mentioning
confidence: 99%
“…To our knowledge, this is the first work to report high mRNA levels of SERT and p11 in PBMC from airline pilots. Both genes are related to depression ( 16 , 19 ) and play key roles in the functioning and regulation of the serotonergic system ( 35 , 36 ). A dysfunctional serotonergic system leads to abnormal neurotransmission and the development of psychiatric disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Sodium binding is the first step of the transport cycle, because the high extracellular NaCl concentration leads to fast binding. The outward-facing state is stabilized by sodium binding and the affinity of the substrate increases strongly with the presence of Na + ( Keshet et al, 1995 ; Mager et al, 1996 ; Lu and Hilgemann, 1999a ; Lu and Hilgemann, 1999b ; Kanner, 2003 ; Szollosi and Stockner, 2021 ; Szollosi and Stockner, 2022 ).…”
Section: Gaba Transporter Structurementioning
confidence: 99%